2023
DOI: 10.1186/s13018-023-03977-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of transverse connectors on total en bloc spondylectomy of the lumbar spine: a finite element analysis

Abstract: Background The influence of total en bloc spondylectomy (TES) on spinal stability is substantial, necessitating strong fixation to restore spinal stability. The transverse connector (TC) serves as a posterior spinal instrumentation that connects the left and right sides of the pedicle screw-rod system. Several studies have highlighted the potential of a TC in enhancing the stability of the fixed segments. However, contradictory results have suggested that a TC not only fails to improve the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, an IPDs is one kind of spinal fusion device widely used for lumbar spinal stenosis is the reason for undergoing spinal surgery for bony decompression by DIAM™ device. Multiple studies have shown better long-term clinical outcomes of surgeries with the DIAM™ device [2]. Among the placement of flexible IPDs, DIAM™ is a relatively newer spinal fusion surgery technology on the implantation of DIAM™ spinal fixation [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, an IPDs is one kind of spinal fusion device widely used for lumbar spinal stenosis is the reason for undergoing spinal surgery for bony decompression by DIAM™ device. Multiple studies have shown better long-term clinical outcomes of surgeries with the DIAM™ device [2]. Among the placement of flexible IPDs, DIAM™ is a relatively newer spinal fusion surgery technology on the implantation of DIAM™ spinal fixation [3].…”
Section: Introductionmentioning
confidence: 99%